2013
DOI: 10.2174/18746098112059990034
|View full text |Cite
|
Sign up to set email alerts
|

Increased Protein Oxidation and Loss of Protein-Bound Sialic Acid in Hepatic Tissues of D-galactose Induced Aged Rats

Abstract: A redox basis of the increased oxidative protein damage and free radical-mediated desialylation have not been fully elucidated in aging. It is well known that the incidence of several liver diseases increase with age. This original research focuses on protein oxidation mechanisms and protein-bound sialic acid levels in liver tissue of the mimetic aging rats. Injection of D-galactose (60 mg/kg/day) for six weeks to male Sprague-Dawley rats (20-week-old) used to establish mimetic aging model. We investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A role for oxidative damage in mimetic aging is mainly supported by studies in rodents (Yanar et al., ; Aydin et al., ; Çakatay et al., ). Increased oxidative protein damage and free radical mediated desialylation of cellular proteins is another important mechanism for cellular aging in rodents (Çakatay et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A role for oxidative damage in mimetic aging is mainly supported by studies in rodents (Yanar et al., ; Aydin et al., ; Çakatay et al., ). Increased oxidative protein damage and free radical mediated desialylation of cellular proteins is another important mechanism for cellular aging in rodents (Çakatay et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A role for oxidative damage in mimetic aging is mainly supported by studies in rodents (Yanar et al., ; Aydin et al., ; Çakatay et al., ). Increased oxidative protein damage and free radical mediated desialylation of cellular proteins is another important mechanism for cellular aging in rodents (Çakatay et al., ). On the other hand, Drosophila is used widely to examine the relationship between oxidative stress and aging (Cui et al., ; Lushchak et al., ; Yamamato et al., ) because Drosophila genetic systems are well known and postmitotic tissues (Clancy and Birdsall, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the young larval stage (5 th instar) and in the oldest stage (motionless prepupa), Sias were observed to be 20-and 10-fold decreased, respectively. Since Sias represent complex glycosylation, these values indicated that complex glycosylation of glycoproteins presents mostly in younger mammal individuals [45,[75][76][77][78][79][80][81][82][83][84][85].…”
Section: Stages Lectin Lectinmentioning
confidence: 99%
“…This mimetic aging model was related to the formation of age‐related advanced glycation end products, which can accelerate oxidative tissue damage, abnormal stress, excessive inflammation, and cell apoptosis and affect learning and memory functions(Shoji, Takao, Hattori, & Miyakawa, 2016). In addition, brains and livers of mice are believed to be particularly susceptible to oxidative stress and dysfunction in D‐galactose treatment (Cakatay et al., 2013; Chen, Zhong, Peng, Sun, & Kong, 2010). This work investigates the antifatigue and antiaging properties of CRW in mice, which would provide more clues to explain the healthy functions of CRW.…”
Section: Introductionmentioning
confidence: 99%